Changes in mental fatigue across preparation and competition periods in elite male Australian football players - Joseph, S. D.; Russell, S.; Halson, S. L.; Johnston, R. D.; Timmins, R. G.; Murray, N. B.; Griffith, S.; Cormack, S. J. (Journal of Sports Sciences, 2025)
This study aimed to measure perceived mental fatigue (MF) across a season in elite male Australian Football (AF) athletes and identify if physical fatigue (PF) or sleep quality (SQ) are associated with perceived MF. Twenty-four elite male AF athletes (25.2 ± 4.4y) rated their MF and PF on visual analogue scales and SQ on a Likert scale each training day of a 38-week season, defined into 7 periods. Linear mixed models determined differences in MF between periods, along with potential relationships of PF and SQ on MF. Repeated measures correlations determined shared variance between MF, PF and SQ. MF was significantly higher Pre-Christmas (baseline) compared to Early In-Season (p < 0.001), Early-Mid In-Season, Late-Mid In-Season and Late In-Season (all p < 0.01). Small effect sizes were observed between Pre-Christmas and Transition, Early In-Season, Early-Mid In-Season, Late-Mid In-Season and Late In-Season MF. Significant interactions were noted between MF and PF (p < 0.001) and MF and SQ (p < 0.01). A positive relationship between MF and PF (r = 0.55, p < 0.001) and inverse relationship between MF and SQ (r=-0.17, p < 0.001) were observed. Perceived MF was highest at the beginning of preparation phase of the season, while increased PF and decreased perceived SQ related to increased perceived MF in elite AF athletes.